COMPUTER PROGNOSIS OF BIOLOGICAL ACTIVITY FOR A NUMBER OF NEW 7-R-8-SUBSTITUTED-1,3-DIMETHYL-XANTHINE - Korobko, Dmytro; Logoyda, Liliya; Markiv, Ihor; Berdey, Ihor (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Abstract Creation of new potential active pharmaceutical ingredients of synthetic origin is an urgent problem of modern medical chemistry. With this purpose was obtained a number of original 7,8-disubstituted theophylline, and some molecular and pharmacological descriptors are calculated using public Web-resource Chemicalize.org. There was shown the influence of respective substituents in 7 and 8 positions of molecules of synthesized substances on druglike and was confirmed the prospects of chosen area of study. Â  Keywords: virtual analysis, 7,8-disubstituted 1,3-dimethylxanthine, druglike, Ghosh, Maggie and Weber filters.Â 